ABSURD AS LOVE OF TERRESTRIAL LOVE IN “OUTSIDER BY ALBERT CAMUS - Tamar Gagoshidze (European Scientific Journal, ESJ, 2014)
In the twentieth century there were a number of works dedicated to the absurd theme. This trend is kind of a key idea in the French literature among French authors. The authors created the whole gallery of the absurd characters, whereas Camus’ Outsider is one of the major one. On the other hand, one should also note that this subject derives from the ancient times and is part of world literature works.